2020
DOI: 10.1007/s00381-020-04698-0
|View full text |Cite
|
Sign up to set email alerts
|

Atonic seizures in children: a meta-analysis comparing corpus callosotomy to vagus nerve stimulation

Abstract: Purpose Atonic seizures are associated with a particularly poor response to medical treatment. We performed a systematic review and meta-analysis to compare the efficacy of corpus callosotomy (CC) and vagus nerve stimulation (VNS) in the management of atonic seizures in the pediatric population. Methods A literature search was performed in compliance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and recommendations, focusing on atonic seizures, CC, and VNS in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Clinical outcomes and complication probabilities were obtained from recent systematic reviews that synthesize and compare CC and VNS literature. 8,15 Given that LGS patients have multiple seizure types, seizure reduction probabilities were considered as an average of seizure reduction from all seizure types. 8 Seizure freedom and >50% seizure reduction were considered as discrete probabilities; thus, rates of seizure freedom were subtracted from rates of >50% seizure reduction to calculate the probabilities of seizure freedom and >50% seizure reduction.…”
Section: Clinical Variablesmentioning
confidence: 99%
“…Clinical outcomes and complication probabilities were obtained from recent systematic reviews that synthesize and compare CC and VNS literature. 8,15 Given that LGS patients have multiple seizure types, seizure reduction probabilities were considered as an average of seizure reduction from all seizure types. 8 Seizure freedom and >50% seizure reduction were considered as discrete probabilities; thus, rates of seizure freedom were subtracted from rates of >50% seizure reduction to calculate the probabilities of seizure freedom and >50% seizure reduction.…”
Section: Clinical Variablesmentioning
confidence: 99%
“…However, a recent meta-analysis of 31 studies involving 533 children showed that callosotomy was more effective than VNS at a cost of greater adverse events, including twice as many reoperations and a 14% rate of symptomatic disconnection syndrome. 31 A recent meta-analysis reported 38 cases with refractory (RSE) or super-refractory (SRSE) status epilepticus, where limited or no alternative treatments was available, who were treated with VNS, including 28 whose status was controlled. However, RSE/SRSE ceased more than 10 days after implantation in half of these patients, calling into question the role of VNS in controlling status.…”
Section: Vagus Nerve Stimulationmentioning
confidence: 99%
“…There have been several systematic reviews and meta‐analyses of surgeries for DRE, but only two articles have focused on CC (Chan et al., 2018 ; Graham et al., 2016 ), while others have compared CC to other treatments, such as vagus nerve stimulation (VNS) and ketogenic diet (Rolston et al., 2015 ; Sharawat et al., 2021 ; Ye et al., 2021 ). Most reports exploring the surgical results of CC in patients with DRE arise from small case series.…”
Section: Introductionmentioning
confidence: 99%